BUILDING CHARACTER THROUGH NOKEN: LEARNING BASED ON PAPUAN LOCAL WISDOM - Sri Handayani, Winda; Prastiwi, Yeny; Hidayat, Nur (Dialectical Literature and Educational Journal, 2024)
In the era of globalization, character education is an essential to address the growing challenges of cultural identity crises and moral decline. Noken a traditional Papuan craft, represents not only a cultural symbol but also a promising medium for culture-based learning. This study aims to explore the potential of noken as a character education tool and to fill the gap in the literature regarding its integration into formal education. Employing a literature review method, this research analyzes relevant sources such as books, journal articles, and research reports focusing on noken and its role in education. The findings reveal that incorporating noken into learning activities, such as storytelling and crafting, significantly enhances students’ cultural awareness, fosters social values like cooperation and responsibility, and promotes the preservation of Papuan heritage. Additionally, noken-based education encourages empathy, teamwork, and pride in local traditions, contributing to students’ holistic character development. The study concludes that noken can serve as an effective educational tool to shaping students’ strong character and recommendations integrating local cultural values into modern education curricula to ensure their sustainability and relevance